Therapeutic efficacy and drug safety comparison of one-week Vonoprazan triple therapy with two-weeks Esomeprazole triple therapy in Helicobacter pylori infection: Findings from a single-centre randomized clinical trial in population of Pakistan - Farzana Waqar; Mudassar Noor; Ehtesham Haider; Kulsoom Farhat; Shabana Ali; Syedah Fauzia Fatime Gilani (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the therapeutic efficacy and drug safety of Vonoprazan and Esomeprazole triple therapies in Helicobacter pylori infection. Method: The randomised clinical trial was conducted from December 2022 to January 2023 at the Department of Pharmacology, Army Medical College, National University of Medical Sciences, Rawalpindi, Pakistan, in collaboration with the Gastroenterology Department of Pak Emirates Military Hospital, Rawalpindi, and comprised patients found positive for Helicobacter pylori by stool antigen test. They were randomly distributed into two groups. The EAL group received two-week triple therapy with Esomeprazole 20mgand Amoxicillin 1000mg twice daily with Levofloxacin 500mg once daily. The VAL group was prescribed one-week triple therapy with Vonoprazan 20mg and Amoxicillin 1000mg twice daily with Levofloxacin 500mg once daily. Eradication success was evaluated by stool antigen test 4 weeks after starting the treatment. Safety of the therapy was assessed by noting adverse effects at days 3 and 14 of the treatment. Data was analysed using SPSS 27. Results: Of the 122 patients, there were 61(50%) in each of the 2 groups; 30(49.2%) males and 31(50.8%) females with mean age 38.40±12.25 years in group EAL, and 35(57.4%) males and 26(42.6%) females with mean age 40.98±12.13 years in VAL group. In the EAL group, 57(93.4%) patients were found to be free of Helicobacter pylori infection compared to 58(95%) in the VAL group. Nausea 14(23%), bitter taste 41(67.2%), abdominal pain 16(26.2%) and headache 20(32.8%) were the adverse effects that were significantly more common in the EAL group compared to the VAL group B. Conclusion: Vonoprazan-based triple therapy was found to be more effective with less reported adverse effects and potential benefits of better patient compliance due to shorter therapy duration. Clinical Trial Number: Iranian Registry of Clinical Trials: IRCT20221207056738N1. Key Words: Helicobacter pylori, Eradication, Vonoprazan, Esomeprazole, Levofloxacin.